2020
DOI: 10.3390/ph13110331
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Afatinib and Bevacizumab in Untreated EGFR-Mutated Advanced Lung Adenocarcinoma: A Multicenter Observational Study

Abstract: The efficacy of afatinib in combination with bevacizumab in untreated advanced epidermal growth factor receptor (EGFR)-mutated lung adenocarcinoma is currently unclear. We sought to investigate the efficacy of this combination through a multicenter observational analysis. Data for 57 patients with advanced EGFR-mutated lung adenocarcinoma who received afatinib combined with bevacizumab as first-line therapy at the Chang Gung Memorial Hospitals in Linkou and Kaohsiung and Taipei Tzu Chi Hospital from May 2015 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Fourteen (51.8%) of them received re-biopsy, and 8 (57%) patients harbored T790M mutation. Previous clinical trials and real-world data have also confirmed that the combination treatment of EGFR-TKI and anti-angiogenic agents did not influence the frequency of T790M mutation [16,19,21]. In a FLAURA study, NSCLC patients harboring OS than patients with first-generation EGFR-TKIs [8,9].…”
Section: Discussionmentioning
confidence: 86%
“…Fourteen (51.8%) of them received re-biopsy, and 8 (57%) patients harbored T790M mutation. Previous clinical trials and real-world data have also confirmed that the combination treatment of EGFR-TKI and anti-angiogenic agents did not influence the frequency of T790M mutation [16,19,21]. In a FLAURA study, NSCLC patients harboring OS than patients with first-generation EGFR-TKIs [8,9].…”
Section: Discussionmentioning
confidence: 86%
“…The OS analysis of our study showed that exon 19 deletion mutation patients tended to have longer OS than those with the L858R mutation. In the final OS analysis of the NEJ026 trial, patients who received osimertinib as second-line therapy had longer survival than those receiving chemotherapy (50.7 months vs. 40.1 months) [ 39 ]. Together, these findings may explain why the OS of patients with the exon 19 deletion mutation was longer than that of patients with the L858R mutation in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the combination of TKI and antiangiogenic agents for NSCLC patients with EGFR mutation would prolong the progression-free survival (PFS) compared to treating TKI alone group [240][241][242][243][244]. FAK takes part in angiogenesis.…”
Section: Fak Inhibitors In Combination Regimesmentioning
confidence: 99%